The Influence Of E-Procurement On The Performance Effectiveness Of Civil Servants In The Surabaya City Government - Saihon; Kurniawan, Gogi; Hafidulloh (Improvement: Jurnal Manajemen dan Bisnis, 2025)
Technological advancements have encouraged governments to adopt digital systems, including in public procurement processes. However, the effectiveness of e-procurement in improving civil servant performance still requires further investigation, particularly within local government settings. This study aims to examine the impact of e-procurement implementation on the performance of civil servants in the Surabaya City Government. Adopting a quantitative approach, data were collected through a survey of 40 respondents. The results indicate that e-procurement positively influences performance, primarily by transforming work procedures to become more efficient and transparent. In contrast, its influence on the mindset of civil servants remains limited. The findings support the Technology Acceptance Model (TAM) and the Resource-Based View (RBV), emphasizing the importance of organizational readiness, human resource competence, and adaptive work culture in the successful adoption of e-procurement. This research contributes to policy development aimed at strengthening digital governance in the public sector Keywords: Digital Systems, E-Procurement, Civil Servant Performance